O mito de Alexandre, o Grande : breve estudo do Romance de Alexandre Grego - Cohen Rabelo, Laura (2015)
This paper aims to highlight mythical facets in the portrayal of Alexander the Great in some episodes of the Greek Alexander Romance. The analysis will be made considering two aspects: first, discussing the configuration of Alexander as a being of hybrid existence between the human and the divine ?Alexander here has a conflict between his divine offspring (the Egyptian god Amon), and his human frailty, with his untimely death always proclaimed by oracles and premonitions. Then we will analyze how Alexander?s representation is made in an ancient prose narrative, fictionalized around a historical personage, as well as exploring mythological commonplaces, both from the Alexandrian tradition and from other myths. Besides Alexander?s travels throughout the world being endowed with more marvelous aspects than historically narrated wars and expeditions, we also have the depiction of a correspondence of Alexander the Great both with historical characters -as his enemy Darius, king of Persia- and with traditionally mythological characters -like the Amazons. We will consider specifically b -recension of the Greek Alexander Romance, called Life and deeds of Alexander of Macedonia (Bios Alexandrou tou makedónos kaí prákseis). Textual version choice was made knowing that a great variety of recensions and translations of a text of inexact origin and transmission in several languages, an important tradition in the Alexander the Great mythification process in different cultures and throughout the centuries, corresponds to Alexander Romance.